Histopathologic Study of Hansen’s Disease - Dhakhwa, Ramesh; Majagaiyan, Samir; Pradhan, Sailesh (Birat Journal of Health Sciences, 2021)
Introduction: Hansen’s disease is a chronic infectious disease caused by Mycobacterium leprae. Accurate clinical and histopathological diagnosis forms the backbone for appropriate treatment and preventing deformities and drug resistance. Several studies have been conducted on clinical presentation of leprosy however there is a paucity of leprosy related histopathological data from Nepal. Objectives: The objectives of this study were to evaluate histopathological features of leprosy in skin biopsies, categorize them into various types based on Ridley Jopling classification and to correlate with clinical presentations. Methodology: Ninety six skin biopsies histologically diagnosed cases of leprosy from 16th October 2020 to 15th April 2021 were included in the study. Ethical consent was taken from the Institutional Review Committee of KMCTH (Ref.:011020202005). Hematoxylin and Eosin stain was used to study histopathological details. Wade- Fite stain was used to evaluate Bacillary index. The lesions were classified as per the Ridley-Jopling classification. Histopathologic findings were correlated with clinical diagnosis. Results: Male to female ratio of patients was 2.4:1. Most of the cases were seen in the third decade of life (39.6%). Most of the cases presented clinically as papules, nodules and hypoaesthetic patches involving predominantly extremities of the body. Commonest histological diagnosis was Borderline Tuberculoid (BT) leprosy (31/96). All cases of Lepromatous leprosy (LL) showed Acid Fast Bacilli on Wade- Fite stain. Tuberculoid leprosy cases showed granulomas and perineural involvement. Conclusion: Histopathological examination remains the gold standard for definite diagnosis and categorization of Hansen’s disease.